Convenient Acylation of Pyrimidine Derivatives Using Microwave Irradiation - MOBINIKHALEDI, A.; FORUGHIFAR, N.; HABIBI, M.; KALATE, Z. (Asian Journal of Chemistry, 2010)
N-Acylated ethyl-6-methyl-4-aryl-2-oxo (or thioxo )-1,2,3,4-tetrahydropyrimidine-5-carboxylate (2a-f) and 6-methyl-4-aryl-2-oxo (or thioxo )-1,2,3,4-tetrahydropyrimidine-5-methylketone (2g-h) were synthesized by the reaction of an appropriate pyrimidine derivative (1) and acetic anyhydride under microwave irradiation. Yields of products following recrystallization from ethanol were of the order of 60-85%.